The professional valeological portrait of instructor of physical culture - Semanyshyn, T.M.; Popel, S.L. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: identify components of the readiness of the future physical education specialist to valeological activity in preschool education. Material : a review and theoretical analysis of the scientific literature. Results : defines the general and special competence, the individual components. The degree of their relationship in the process of preparing an instructor of physical education in preschool education. Theoretically proved that the readiness of the future specialist organization based on skill valeological activities (including major tasks specific functions and values valeological culture). Such an organization implies unity of general and special components health-preserving technologies. Conclusions : the process of forming a professional portrait valeological instructor in physical education in pre-school educational institution should provide its willingness to valeological activities. This is based on the awareness of its organization and unity of general and special health- technology components.